Executive functioning in obese individuals waiting for clinical treatment - Gameiro, Fátima (2021)
Background: Executive functions have an important role in human behavioural regulation and can be a determinant of eating behaviour. Our aim was to study the different components of executive functions in obese individuals waiting for clinical treatment, comparing them with normoweight subjects with similar socio-demographic characteristics. Method: A total of 114 adults (76 obese and 38 normoweight) completed a neuropsychological battery that included tasks of conceptualization and abstraction, motor programming, response maintenance, inhibition and resistance, problem solving, cognitive fl exibility, and verbal fl uency. Results: There was a statistically signifi cant difference between groups for all the dimensions of the executive functions evaluated, with the obese group showing poorer performance compared to normoweight. Conclusions: Obese individuals demonstrated poorer executive functions than normoweight individuals.